Impact of FaSSIF on the solubility and dissolution-/permeation rate of a poorly water-soluble compound - Frank, Kerstin J.; Fricker, Gert (European journal of pharmaceutical sciences, 2012)
The poorly water-soluble drug ABT-102, a potent TRPV1 (transient receptor potential cation channel subfamily V member 1) antagonist, was investigated in terms of its solubility and dissolution-permeation rate across Caco-2 cell monolayers in the presence and absence of fasted state simulated intestinal fluid (FaSSIF). ABT-102 showed a more than 30-fold higher apparent solubility in FaSSIF, compared to Hank’s balanced salt solution (HBSS). On the other hand, the amount of truly dissolved API in the suspension, as assessed by inverse dialysis, was found hardly influenced by FaSSIF. Neither the drug nor FaSSIF adversely affected cell viability or integrity of the Caco-2 monolayer. P-gp-inhibition experiments confirmed that the drug was not a substrate of the export pump. The flux of ABT-102 across the Caco-2 barrier was found virtually the same in FaSSIF and in buffer, i.e. in vitro overall dissolution-/permeation rate of ABT-102 from suspensions appears not affected by its enhanced apparent solubility due to association with TC/PC-micelles.